Whole-Farm Planning for Economic and Environmental Sustainability - Janke, Rhonda R. (My University, 2000)
This publication provides information for whole-farm planning for economic and enivorinmental sustainablitty.
MF2403_2000-08
Keywords: MF2403; Economics; Environment and Natural Resources; MF